Evaluation of Effective Factors in Success Rate of Intervention on CTO - Mohammadhasan Namazi; Morteza Safi; Hosein Vakili; Habibollah Saadat; Saeed Alipour; Parsa Mahjoob; Maryam Taherkhani; Shamseddin Pedari; Mehrdad Taherion; Hasan Rajabi Moghaddam; Abdolkarim Alhazifi; Masoume Vatanparast; et al. (Acta Medica Iranica, 2015)
Chronic total occlusion (CTO) intervention is still a challenging problem. The aim of this study is to determine factors that affect PCI results.The study was conducted on 72 patients in two centers. CTO angioplasty was done by the antegrade approach from the femoral and/or radial approach. The role of age, gender, anatomical variations such as calcification, length of the lesion, proximal bending, retrograde filling and occluded coronary artery (LAD, CCK or RCA), and wires were assessed. The success rate was 79.6%, and presence of calcification was an important factor in CTO PCI. Operator's experience, use of appropriate equipment and calcification are important factors in predicting a successful PCI.